The Dilution of Identity in the Artistic Concept of Emma Andijewska - ZYMOMRYA , Ivan (Transfer. Reception Studies, 2019)
The article considers the dilution of identity in the artistic concept of the Ukrainian writer Emma Andijewska, where creating a cultural identity has become a particularly important issue in her literary heritage. She belongs to those writers who have created their own literary discourse around reflecting the inner spirituality of human feelings. Each book by Emma Andijewska also contains contradictory motifs appropriate as representative of immigration literature. Emma Andijewska lived and created in countries with different socio-economic conditions. Being in exile – in Germany, France and the United States – she never felt isolated from her home country as she always considered herself a Ukrainian. The drama of actions committed by her protagonists is that they cannot and do not want to get rid of the heightened sense of belonging to their nation while not being able to live in their native land. In the "Novels About Human Destiny", the author motivates the psychological states of her heroes through the prism of nationality, genetic and cultural memory, as well as extreme and brink situations. The artistic world of Emma Andijewska primarily reflects universal manifestations related to specific facts, life events and realities. The direct foundations of her creative practice appears from the observation and interpretation of the author’s experience in conditions of migration.